2021
DOI: 10.1002/art.41551
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Remission of Granulomatosis With Polyangiitis After Discontinuation of Glucocorticoids and Immunosuppressant Therapy: Data From the French Vasculitis Study Group Registry

Abstract: Objective. Data on sustained remission of granulomatosis with polyangiitis (GPA) after discontinuation of therapy (referred to as GPA with sustained remission off-therapy [SROT]) are scarce. In the present study, SROT among GPA patients from the French Vasculitis Study Group Registry was evaluated to identify factors associated with its occurrence and durability. Methods. For inclusion of patients in the study, the diagnosis of GPA had to meet the GPA classification criteria defined by the American College of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Our 546 PR3-ANCA–positive GPA patients represent one of the largest groups yet constituted, with median follow-up exceeding 3 years, enabling identification of long-term outcomes with a sufficient level of evidence 14 32. Compared with the other subsets, PR3-positive patients’ RFS rate was lower.…”
Section: Discussionmentioning
confidence: 97%
“…Our 546 PR3-ANCA–positive GPA patients represent one of the largest groups yet constituted, with median follow-up exceeding 3 years, enabling identification of long-term outcomes with a sufficient level of evidence 14 32. Compared with the other subsets, PR3-positive patients’ RFS rate was lower.…”
Section: Discussionmentioning
confidence: 97%
“…Frequently relapsed patients are hard-to-manage patients and it was shown that RTX therapy is effective and safe for chronic relapse patients for the induction of remission and maintaining the remission [ 101 ]. The effectiveness of maintenance therapy was also suggested by evaluating 795 GPA patients from the French Vasculitis Study Group Registry; it was shown that RTX maintenance therapy can remarkably help to achieve sustained remission (≥6 months) off therapy [ 102 ]. In another study including 66 GPA patients who received 500 mg RTX every six months until month 18, in a 34.2 ± 26.2-month follow-up, the relapse rate was 11.2/100 patient years.…”
Section: Resultsmentioning
confidence: 99%
“…One such study was recently conducted by the French Vasculitis Study Group, which evaluated sustained remission of GPA after discontinuing therapy. 18 Similar observational studies are of great value as discontinuation of therapy is a likely possibility after remission, but very little is known about this aspect of GPA treatment.…”
Section: Discussionmentioning
confidence: 99%